Agreements and disagreements in the narrative constructions of D. Pedro II and the Second Reign (RIHGB-1925): Concordâncias e discordâncias nas construções narrativas de D. Pedro II e do Segundo Reinado (RIHGB-1925) (Revista de História da UEG (REVHIST), 2023)
In the 19th century, the Instituto Histórico e Geográfico Brasileiro (IHGB) became an institutional place responsible for taking care of the project of writing the history of the nation guided by a proposal linked to the monarchical State. From 1889, how to dissolve the imperial regime and establish the Republic, where the IHGB redefines, recreates and uses new practices to narrate history. Even in the Republic, the intellectual stronghold still retained traces of the monarchical regime and the imperial figure still hovered over the Institute. As an example of this, the faith organized a commemorative volume of the birth of D. Pedro II in the Magazine of the Brazilian Historical and Geographical Institute (RIHGB) in 1925. In this sense, the article aims to present the dialogues between the others in the Magazine of certain tactics and highlight the approximations and departures of ideas about the memory/history of D. Pedro II and the Second Empire. For this, we seek to analyze some of the main narratives in order to map the points of agreement/agreement and disagreement/disagreement of ideas by the authors. Through this study, we seek to understand how the memory/history of the Empire and the Emperor were constructed in dispute by the authors in the RIHGB narratives in 1925.Keywords: D. Pedro II. RIHGB. History of Historiography.